The complete idiot's guide to Shakespeare - Rozakis, Laurie (Alpha Books, a division of Macmillan General Reference, 1999)
"Introduces Shakespeare's plays, sonnets, and narrative poems, and discusses major themes, characters, and dramatic techniques."